¹H, ¹³C and ¹⁵N resonance assignments for the fibrillin-1 EGF2-EGF3-hybrid1-cbEGF1 four-domain fragment. - Robertson, I; Osuch, I; Yadin, D; Handford, P; Jensen, SA; Redfield, C (2014)
Fibrillins are large extracellular glycoproteins that form the principal component of microfibrils. These perform a vital structural function in the extracellular matrix of many tissues. Fibrillins have also been implicated in mediating a number of protein-protein interactions, some of which may be significant in regulating growth factors such as transforming growth factor β. Here we present the backbone and side-chain (1)H, (13)C and (15)N assignments for a 19 kDa protein fragment derived from the N-terminus of human fibrillin-1, encompassing four domains in total. These domains include the second and third epidermal growth factor-like (EGF) domains, the first hybrid domain (hyb1), and the first calcium-binding EGF domain of fibrillin-1. This region of fibrillin-1 is of particular interest as the hyb1 domain has been suggested to play a role in microfibril assembly, as well as several other protein-protein interactions.